The body and female identity in Eithne Strong’s Flesh: The Greatest Sin - Chang, Hawk (Penerbit Universiti Kebangsaan Malaysia, 2017)
Bodily discourse, constantly appropriated as a symbol of Irish famine and hunger in the wake of British maladministration of the land and its people since the Great Famine, is prevalent in Irish culture. However, this bodily discourse is dominated by nationalistic and patriarchal narratives. An increasing number of women in contemporary Ireland look at themselves anew through their own bodies. Through the reading of Eithne Strong’s poetry collection, Flesh: The Greatest Sin (1980), this paper discusses how the conflation of body and sin is entangled in the Irish context, how the female writer manages to untangle the fine line fabricated between the two categories and reaffirm her female identity simultaneously, and finally the significance of such an attempt in the history of Irish literature.